From COCU To CUiC: The Struggle for Reconciliation and Faithfulness - Crow, Paul A. (The journal of Presbyterian history, 2006)
The Consultation on Church Union (COCU) came into existence in response to Eugene Carson Blake's December 1960 sermon, “A Proposal Toward the Reunion of Christ's Church," evoking hope for reconciliation among nine diverse churches. However, the 1970 A Plan of Union for the Church of Christ Uniting produced general anxiety over the proposed structures. The COCU Consensus: In Quest of a Church of Christ Uniting (1988), offered a new form of church unity, “covenant communion," which carried a commitment to overcoming racism, sexism, and handicapism. COCU's 1999 plenary revealed that the Presbyterian and Episcopal churches were not ready to address reconciliation of ordained ministries, so in January 1999, COCU's members approved the other seven elements of covenant communion. Under the new name Churches Uniting in Christ (CUIC), member churches entered into a new expression of visible unity, giving priority to overcoming racism in the churches and American society. Current crises among mainline Protestant churches challenge CUIC's vision, and the struggle continues.